Programa “Ideas Quim” y la capacidad comprende y aplica conocimientos científicos en estudiantes del tercer grado de la Institución Educativa “Agro Industrial 128” de Conima, Moho –Puno, 2018 - Ajahuana Mamani, Felipa (2019)
The objective of this research is to improve student learning, through the Ideas Quim program it is sought to determine the influence on capacity includes and applies scientific knowledge in the third grade students of the Secondary Educational Institution Agro Industrial 128 Conima in the Moho province, in Puno._x000D_ The Ideas Quim program is a set of twelve sessions, which presents the development of visual organizers as a characteristic; in the development of the program a series of readings, practical exercises, selection of key words, projection of videos and short experiments are made, then a synthesis is made in visual organizers, as well as the cause - effect diagram, conceptual maps and mental maps; Finally, the students explain what they have understood by making use of the visual organizer created by them._x000D_ The research was of quantitative and pre-experimental design approach with a population of 98 students, a measurement instrument was applied, the development test, to a sample of 23 students, then the Ideas Quim program was applied and then the instrument was used of output measurement .; the data processing, gave as results in the pre-test the dimensions comprise and apply 3.04 and 2.09 respectively, with these scores are located at the pre-start achievement level and a total score of 5.13 in the nominated variable capacity comprises and applies scientific knowledge, which definitely places the group of students at the pre-start achievement level. After the application of the Ideas Quim program was obtained in the dimensions comprised and applied 8.70 and 8.39 respectively, placing the students at the level of achievement of process and satisfactory and a total score of 17,09 in the variable called capacity understands and applies scientific knowledge.